2018
DOI: 10.1038/s41524-018-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic composition on thermal properties of energetic ionic liquids

Abstract: A model to predict the effect of ionic composition on the thermal properties of energetic ionic liquids was developed by quantitative structure-property relationship modeling, which predicted the detonation velocity, pressure, and melting temperature of energetic ionic liquids. A hybrid approach was used to determine the optimal subset of descriptors by combining regression with the genetic algorithm as an optimization method. The model showed the high accuracy, reaching a correlation factor of R 2 as 0.71, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Indeed, onedimensional polymeric model systems showing different conjugation paths (para-, ortho-and meta) and configurations (cis and trans for meta cases) have been also considered, carrying out periodic boundary conditions DFT calculations at the same level of theory using the CRYSTAL17 code [37][38][39] to fully optimize their geometry and computed the band-gap. The same computational setup has been adopted in a previous work to study 2D g-GDY and related nanoribbons [46]. For the optimizations of the 1D polymers the tolerance on integral screening (TOLINTEG parameters) have been fixed to 9,9,9,9,80, while the shrink parameters defining Monkhorst-Pack sampling points have been fixed to 50.…”
Section: Figure 1: A) Sketches Of Para Meta and Ortho Conjugation Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, onedimensional polymeric model systems showing different conjugation paths (para-, ortho-and meta) and configurations (cis and trans for meta cases) have been also considered, carrying out periodic boundary conditions DFT calculations at the same level of theory using the CRYSTAL17 code [37][38][39] to fully optimize their geometry and computed the band-gap. The same computational setup has been adopted in a previous work to study 2D g-GDY and related nanoribbons [46]. For the optimizations of the 1D polymers the tolerance on integral screening (TOLINTEG parameters) have been fixed to 9,9,9,9,80, while the shrink parameters defining Monkhorst-Pack sampling points have been fixed to 50.…”
Section: Figure 1: A) Sketches Of Para Meta and Ortho Conjugation Pat...mentioning
confidence: 99%
“…GDY crystals share with other polyconjugated materials the large impact structural effects and peculiar topology can have on their properties by strongly modulating the electronic, optical and vibrational response [26][27][28][29][30][31]. Topological effects in hybrid sp-sp 2 carbon materials have been investigated and discussed also very recently [45][46], having a strong relevance for the design, modulation and tuning of the material properties in view of potential technological applications. In the case of GY, molecular fragments made by aromatic rings connected with monoacetylenic units were theoretically studied for the first time by Tahara and coworkers [40], analyzing the effect of connectivity and topology on electronic and aromatic properties of deydrobenzoannulenes (DBAs).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the anisotropic band dispersions can be induced in graphene through external Periodic Potentials 42,43 or elemental doping 45 . In fact, intrinsic anisotropic Dirac-cones can be realized through graphene allotropes 23,32,33 and graphyne allotropes 31,41,46,47 , such as OPG-Z 33 , phagraphene 32 and SW-graphene 23 . However, the anisotropies of the Diraccones are usually not very strong.…”
mentioning
confidence: 99%
“…Early theoretical studies on GY-and GDY-based systems were reported in 1987 15 and more recently modern computational methods have been employed to shed light on their properties. [16][17][18][19][20] These structures can be classified as covalent organic frameworks (COFs), showing the occurrence of Dirac cones, flat bands, and tunable bandgap. 21,22 Such features of the electronic structure of COFs have been explained based on peculiar topological effects also in connection to their influence on the charge transport behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Early theoretical studies on GY- and GDY-based systems were reported in 1987 15 and more recently modern computational methods have been employed to shed light on their properties. 16–20…”
Section: Introductionmentioning
confidence: 99%